2023
DOI: 10.1177/21925682231156558
|View full text |Cite
|
Sign up to set email alerts
|

Does Erector Spinae Plane Block Decrease Analgesia Requirements After Minimal-Invasive Posterior Transpedicular Stabilization in Patients With Vertebral Body Fracture? A Prospective, Randomized, Double-Blind Controlled Study

Abstract: Study design Prospective randomized placebo controlled double blind trial. Objective To examine the effect of ESP block after minimally invasive posterior stabilization for vertebral fractures on opioid consumption, pain, blood loss, disability level, and wound healing complications. Methodology Patients indicated for minimal invasive posterior stabilisation were included to the study. Our primary outcome was the opioid consumption and Visual Analogue Scale (VAS) measured during the first 48 hours. Secondary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Among the remaining 48 articles, 16 were excluded after full-text review. Finally, 32 RCTs 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 involving a total of 2146 patients (ESPB group/Control group = 1077/1069) were included in our meta-analysis. PRISMA flow diagram of the study selection is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the remaining 48 articles, 16 were excluded after full-text review. Finally, 32 RCTs 11 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 involving a total of 2146 patients (ESPB group/Control group = 1077/1069) were included in our meta-analysis. PRISMA flow diagram of the study selection is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 48 , 49 Over the past few years, it has been increasing recognised as a simple component of peri-operative MMA in patients undergoing spinal surgery. 40 Over the recent years, although multiple prospective trials have been published; the availability of systematic reviews or meta-analysis on this subject is fairly limited. The current meta-analysis was thus planned to comprehensively analyse the present literature; and put forth the best available evidence regarding bilateral ESPB as a pre-emptive analgesic modality in patients undergoing spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Letter to the Editor Concerning "Does Erector Spinae Plane Block Decrease Analgesia Requirements after Minimal-Invasive Posterior Transpedicular Stabilization in Patients with Vertebral Body Fracture?" Pravesh S. Gadjradj, MD, PhD, MSc 1 , Sean Cofano, MD 2 , Fabian Sommer, MD 1 , Mateusz Bielecki, MD 1 , Rodrigo Navarro-Ramirez, MD 3 , and Judith de Rooij, PhD 4 To the Editor Its with great interest that we read the paper by Holas et al investigating the effectiveness of an Erector Spinae Plane Block (ESPB) on postoperative opioid consumption and pain as measured on the visual analogue scale (VAS) in a randomized, placebo controlled, double blind trial in patients undergoing a minimally invasive posterior stabilization. 1 The authors included a total of 60 patients and concluded that the ESPB reduced the opioid consumption during PACU stay by 38% and reduced the VAS.…”
mentioning
confidence: 99%
“…Pravesh S. Gadjradj, MD, PhD, MSc 1 , Sean Cofano, MD 2 , Fabian Sommer, MD 1 , Mateusz Bielecki, MD 1 , Rodrigo Navarro-Ramirez, MD 3 , and Judith de Rooij, PhD 4 To the Editor Its with great interest that we read the paper by Holas et al investigating the effectiveness of an Erector Spinae Plane Block (ESPB) on postoperative opioid consumption and pain as measured on the visual analogue scale (VAS) in a randomized, placebo controlled, double blind trial in patients undergoing a minimally invasive posterior stabilization. 1 The authors included a total of 60 patients and concluded that the ESPB reduced the opioid consumption during PACU stay by 38% and reduced the VAS. Even though we appreciate the paper by Holas et al and its potential role in combatting the opioid crisis, some methodological issues need to be discussed or clarified.…”
mentioning
confidence: 99%